2015
DOI: 10.1134/s1607672915050178
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin causes transient activation of protein poly(ADP-ribosyl)ation in H9c2 cardiomyocytes

Abstract: Possible involvement of the system of protein poly(ADP-ribosyl)ation in the mechanisms of cardiotoxicity of doxorubicin, one of the most frequently used anticancer drug, was studied in cultures of cardiomyocytes H9c2. The treatment of H9c2 cells with doxorubicin (1 µM) led to a transient (after 6 h of incubation) increase in the nuclear level of poly(ADP-ribosyl)ated proteins. The observed data indirectly indicate the development of genotoxic stress in the doxorubicin-treated cells, probably caused by the stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recently, we have reported that the increased PARylation level of FoxO3 play a crucial role in ISO-caused cardiac hypertrophy in vivo and in vitro 37 . Over-activation of PARP1 exerts a critical effect on the cardiac dysfunction in DOX-cardiomyopathy 44 . The PARylated protein levels were dramatically induced by DOX in the cardiomyocytes44, 45, 46, 47. Inhibition of PARP protects against DOX-induced myocardial apoptosis and heart injury44, 47.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that the increased PARylation level of FoxO3 play a crucial role in ISO-caused cardiac hypertrophy in vivo and in vitro 37 . Over-activation of PARP1 exerts a critical effect on the cardiac dysfunction in DOX-cardiomyopathy 44 . The PARylated protein levels were dramatically induced by DOX in the cardiomyocytes44, 45, 46, 47. Inhibition of PARP protects against DOX-induced myocardial apoptosis and heart injury44, 47.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, activation of PARP1 contributes to the various cardiovascular diseases, which were accompanied by the increased PARylated-target proteins, NAD repletion and sirtuins inactivation44, 45, 46, 47, 52, 53, 54 Previous papers from our laboratory demonstrated that PARP1 is strongly activated by AngII or isoproterenol (ISO), meanwhile its novel inhibitors (salvianolic acid B and AG-690/11026014) protect the myocardium from Ang II-stressed hypertrophy in vitro and in vivo 55, 56, 57, 58. Recently, we have reported that the increased PARylation level of FoxO3 play a crucial role in ISO-caused cardiac hypertrophy in vivo and in vitro 37 . Over-activation of PARP1 exerts a critical effect on the cardiac dysfunction in DOX-cardiomyopathy 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation